The finite element analysis of ductile damage during hot stamping of 22MnB5 steel. (15th March 2015) - Hu, Ping; Shi, Dongyong; Ying, Liang; Shen, Guozhe; Liu, Wenquan
Highlights: The effects of temperature and strain rate on hot ductility of 22MnB5. We derive the constitutive equations coupled with damage for hot stamping. The damage parameters sensitive to temperature and strain rate were identified. The effects of blank holding force and friction on formability, damage evolution and punch force. Abstract: This study deals with the finite element investigation of hot stamping of high strength steel. The main objective is to predict when and where the crack can appear in the work-piece during the hot stamping operation. A set of thermo-elastic–plastic constitutive equations coupled with material damage is presented in detail based on continuum damage mechanics. The damage parameters involved in the constitutive equations were determined from uniaxial tensile experimental data of 22MnB5 steel at a temperature range of 650–800 °C and strain rates of 0.01, 0.1, 1.0 s −1 . Using the calibrated constitutive equations, a finite element program was developed based on dynamic explicit algorithm and applied to simulate the deformation process and ductile damage of 22MnB5 under hot stamping conditions. The capability of the program as a predictive tool has been evaluated by comparing experimental and calculated results of the hot stamping process of an automotive B-pillar. And the effects of blank holding force and friction on formability, damage evolution and punch force were analyzed.